Improving the Understanding of Weight Interceptional Relationships Through The Implementation Of The Basic School-Based Discovery Learning Model - Rosidah, Rosidah (Universitas Sebelas Maret, 2020)
Purpose this research to find out the application of TPACK-based discovery learning model can increase the participation of students and efforts to increase understanding of concepts in Mathematics Learning About the Relationship Between Weight Units. The data collection technique is carried out systematically with standard procedures, namely, learning outcome data is taken through tests at the end of each cycle and observation of student participation. The data were analyzed using quantitative and qualitative analyzes of the formative test results. Then, the results of the calculations were consulted with the success criteria, to determine whether they were complete or not. Based on the results of the evaluation test from the first and second cycles, an increase in learning completeness was obtained. In the first cycle achieved learning outcomes with 43% completeness. In the second cycle the completeness of learningoutcomes was 71%. Based on the findings and the results obtained in the study, it can be concluded that, through the TPACK-based discovery learning model, it can increase students' participation and understanding of the concept of students in Mathematics learning about the Relationship between Weight Units but it still needs to be improved in cycle III.